70.1: High‐Resolution OLED Display with the World's Lowest Level of Power Consumption Using Blue/Yellow Tandem Structure and RGBY Subpixels. Issue 1 (June 2015) - Yamaoka, Ryohei; Sasaki, Toshiki; Kataishi, Riho; Miyairi, Noriko; Kusunoki, Koji; Kaneyasu, Makoto; Miyake, Hiroyuki; Ohsawa, Nobuharu; Seo, Satoshi; Hirakata, Yoshiharu; Yamazaki, Shunpei; Ono, Koji; et al.
Abstract : A top‐emission organic light‐emitting diode (OLED) with a a microcavity structure combined with a blue/yellow tandem structure was developed. A high‐resolution active‐matrix OLED display with the world's lowest level of power consumption using the tandem OLED with red, green, blue, and yellow subpixels was fabricated.